Advances in industrial and labor relations. Vol. 12 - Lewin, David, 1943-; Kaufman, Bruce E. (Emerald, 2003)
This volume contains papers dealing with topics such as the effects of company unions on wages, the effects of labour market regulation on hiring standards, coalition bargaining at General Electric, cooperative labour-management partnerships in the steel industry, the union commitment of adjunct faculty, the effects of union political outreach on union members political perceptions, preferences and voting behaviour, reinterpretation of new labour historians differences with old labour historians, and newly discovered lecture notes by industrial relations scholar Sumner Slichter that detail his views on the early development of welfare capitalism in the US. These papers contain a vibrant mix of disciplinary perspectives, analytical methods, arguments and conclusions about key industrial relations topics - and do so from both contemporary and historical perspectives. The volume should be of interest to industrial relations scholars and students worldwide.
Volume 12 of this title contains eight papers that deal with contemporary and historical aspects of unionism and other forms of union and labour representation.
Keywords: Industrial relations.; elektronické knihy; electronic books